WE43 rare earth magnesium alloy and stepped heat treatment method thereof
Through the step heat treatment method of WE43 rare earth magnesium alloy, the problem of insufficient ductility and deformation ability of magnesium alloy is solved, the effect of improving its strength and plasticity is achieved, and the cost is reduced.
Patent Information
- Application Number
- CN202411421037.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-10
AI Technical Summary
Magnesium alloys are prone to dendrite segregation and regional segregation during casting, resulting in reduced ductility and deformability. It is difficult for existing heat treatment methods to effectively improve their strength and plasticity.
The step heat treatment method of WE43 rare earth magnesium alloy includes solid solution treatment and artificial aging treatment. The specific steps are to heat it to 500-550℃ in quartz sand for 4 to 12 hours, and then cool it to 200-300℃ for 10 to 18 hours. , use pyrote to generate a protective atmosphere to prevent oxidation, and reasonably control the grain size and diffusion of alloy elements.
The tensile strength, elongation, toughness and impact resistance of WE43 rare earth magnesium alloy are significantly improved, and good comprehensive performance is obtained, and the cost of use is reduced.
Smart Images

Figure HDA0005080785150000011 
Figure HDA0005080785150000012 
Figure HDA0005080785150000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and in particular relates to a WE43 rare earth magnesium alloy and a step heat treatment method thereof. Background Art
[0002] As the lightest metal in industrial production, magnesium alloy has gradually entered industrial applications in the 1940s. Due to its low density, high specific strength and stiffness, good shock absorption, good electromagnetic shielding and heat dissipation, it is widely used in aerospace, automobile, 3C and other industries, and is known as the "green engineering material of the 21st century."
[0003] During the casting process of magnesium alloys, dendrite segregation and regional segregation are easily formed, which leads to reduced ductility of the material alloy and decreased deformation capacity, making the plasticity of magnesium alloys, which already have poor deformation capacity, even worse. In order to improve the forming properties of magnesium alloys and expand their application range, heat treatment is usually used to make the structure and composition of magnesium alloys uniform. Therefore, establishing the relationship between heat treatment process, structure and performance, and determining the optimal heat treatment process parameters for magnesium alloys has become a hot area of current research.
[0004] The strengthening methods of magnesium alloys mainly include solid solution strengthening, precipitation strengthening, dispersion strengthening, fine grain strengthening and deformation strengthening. The strength and plasticity of magnesium alloys after heat treatment are greatly improved, the internal defects are significantly reduced, and the mechanical properties are significantly improved. Most of the heat treatment processes are through the mechanisms of twinning, grain boundary sliding, recrystallization, etc. in the deformation process of magnesium alloys, as well as crystal defects at the microscopic level, such as dislocations, vacancies, stacking faults, etc. These defects can hinder the movement of dislocations when subjected to external forces, thereby showing the improvement of the mechanical properties of macroscopic materials. At present, the commonly used heat treatment methods for magnesium alloys include solid solution treatment, aging treatment and annealing treatment. For cast Mg-RE series magnesium alloys, solid solution and aging heat treatment methods are mainly used to improve the comprehensive properties of the material to varying degrees. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a step heat treatment method for WE43 rare earth magnesium alloy, so that the treated WE43 rare earth magnesium alloy obtains excellent strength and hardness, as well as greater toughness and impact resistance, and has good comprehensive performance.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The invention provides a WE43 rare earth magnesium alloy. The components thereof are calculated by mass percentage as follows: Y: 3.82%, Zr: 0.43%, Gd: 1.48%, Nd: 2.47%, Ni: 0.001%, Fe: 0.001%, Cu: 0.003%, and the remainder is Mg and unavoidable impurity elements.
[0008] Preferably, the WE43 rare earth magnesium alloy is an extruded WE43 rare earth magnesium alloy.
[0009] The present invention also provides a step heat treatment method for the WE43 rare earth magnesium alloy, comprising the following steps:
[0010] Step 1: burying the WE43 rare earth magnesium alloy in quartz sand, laying pyrite sand on the upper layer, placing the whole in a muffle furnace, and heating for solid solution treatment. The solid solution treatment process includes: heating the WE43 rare earth magnesium alloy to 500-550° C. and then keeping it warm for 4-12 hours;
[0011] Step 2: performing artificial aging treatment on the solution treated WE43 rare earth magnesium alloy, wherein the artificial aging treatment process comprises: cooling the WE43 rare earth magnesium alloy to 200-300° C., keeping the temperature for 10-18 hours, and then placing the alloy in air for natural cooling.
[0012] Preferably, a KSL-1500X box-type muffle furnace is used to carry out solution treatment and aging treatment on the WE43 magnesium alloy, wherein the muffle furnace is a non-vacuum environment. During the heat treatment, the WE43 rare earth magnesium alloy material to be heat treated is buried in fine-grained quartz sand and covered with pyrite, so that the pyrite decomposes at high temperature to generate a protective atmosphere of SO2 to prevent the alloy from oxidizing at high temperature.
[0013] Preferably, the WE43 rare earth magnesium alloy is placed in a DHG-9030A electric heated blast drying oven and kept at 120° C. for 0.5 h before solution treatment.
[0014] Preferably, before the solution treatment of the WE43 rare earth magnesium alloy, the muffle furnace is preheated to 120°C and kept warm for 0.5h to remove all water vapor in the device, in order to prevent the hydrogen generated by the contact between the molten magnesium matrix and water vapor at high temperature from reacting rapidly with the oxygen in the surrounding air, and the rapid vaporization of liquid water, which may lead to explosions, shrinkage defects in the magnesium alloy castings, and other defects that affect the alloy properties.
[0015] Preferably, in step 1, the solution treatment process comprises: heating the WE43 rare earth magnesium alloy to 525° C. and then keeping the temperature for 8 hours.
[0016] Preferably, in step 2, the artificial aging treatment process comprises: cooling the WE43 rare earth magnesium alloy to 250° C. and then keeping the temperature for 14 hours.
[0017] The mechanism of action of the step heat treatment method of WE43 rare earth magnesium alloy in the present invention is as follows:
[0018] During the step heat treatment of WE43 rare earth magnesium alloy, alloy elements will dissolve into the magnesium matrix, and the original magnesium atoms in the matrix will be replaced by alloy element atoms. Due to the different radii of the two atoms, lattice distortion occurs in the magnesium unit cell. When dislocation movement occurs, the lattice distortion will increase the resistance of dislocation movement, which makes the plastic deformation of the alloy more difficult, thus increasing the strength and hardness of the magnesium alloy solid solution. Dispersion strengthening is also often accompanied by it. The high-temperature phase precipitated during the dispersion strengthening process can also improve the performance of the alloy. The tensile strength and elongation of the magnesium alloy treated by this heat treatment are improved, and greater toughness and impact resistance are obtained. In addition, the heating time of the solution treatment of magnesium alloy is generally longer. This is because the diffusion rate of various alloy elements in the alloy is slow due to the structure of the magnesium alloy. In order to ensure that the strengthening phase is completely dissolved, the holding time of the solution treatment needs to be increased.
[0019] In addition, on the basis of ensuring the basic dissolution of the eutectic second phase, the growth of the grain size should be reduced as much as possible. On the one hand, the eutectic dissolution increases the supersaturation of the solid solution, providing sufficient driving force and alloying elements for the nucleation and growth of the precipitated phase; on the other hand, excessive growth of the grain size damages the plasticity and strength of the alloy, and the degree of grain growth needs to be strictly controlled. In addition, if the temperature is too high, the grain boundary is prone to overburning, which greatly damages the mechanical properties of the alloy and needs to be prevented.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention adopts a reasonable heat treatment process (for example, solution treatment × 8h + artificial aging × 14h) to enable the WE43 rare earth magnesium alloy to obtain better strength and hardness, as well as greater toughness and impact resistance. Compared with the untreated WE43 rare earth magnesium alloy, the treated WE43 rare earth magnesium alloy has good comprehensive properties, and the cost of using the WE43 rare earth magnesium alloy is also greatly reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the metallographic phase diagram of the WE43 rare earth magnesium alloy in Example 1.
[0023] Figure 2 This is the metallographic phase diagram of WE43 rare earth magnesium alloy in Example 2.
[0024] Figure 3 This is the metallographic phase diagram of WE43 rare earth magnesium alloy in Example 3.
[0025] Figure 4 : The stress-strain curves of WE43 rare earth magnesium alloy with different solution treatment times in the embodiment.
[0026] Figure 5 1 is the stress-strain curve of WE43 rare earth magnesium alloy with different aging treatment times in the embodiment. DETAILED DESCRIPTION
[0027] The technical solution of the present invention is further described below in conjunction with embodiments.
[0028] The WE43 rare earth magnesium alloy used in the following embodiments has the following components in percentage by mass: Y: 3.82%, Zr: 0.43%, Gd: 1.48%, Nd: 2.47%, Ni: 0.001%, Fe: 0.001%, Cu: 0.003%, and the remainder is Mg and unavoidable impurity elements.
[0029] The following embodiment provides a stepwise heat treatment method for the WE43 rare earth magnesium alloy, comprising the following steps:
[0030] Step 1: burying the WE43 rare earth magnesium alloy in quartz sand, laying pyrite sand on the upper layer, placing the whole in a muffle furnace, and heating for solid solution treatment, that is, heating the WE43 rare earth magnesium alloy to 500-550° C. and then keeping it warm for 4-12 hours;
[0031] Step 2: performing artificial aging treatment on the WE43 rare earth magnesium alloy after the solid solution treatment, that is, cooling the WE43 rare earth magnesium alloy to 200-300° C. and then keeping the temperature for 10-18 hours.
[0032] Among them, in step 1, a rare earth magnesium alloy sample is placed in a KSL-1500X box-type muffle furnace. Since the reactor is not a vacuum environment, in order to prevent the material from oxidizing, this experiment takes fine quartz sand in the crucible, buries the material in the quartz sand, and covers it with pyrite for heat treatment. The samples are heated to 525°C and kept warm for 4h, 6h, 8h, 10h and 12h respectively. By observing and analyzing the microstructure of WE43 magnesium alloy after solution treatment, combined with its mechanical properties, it is determined that the optimal solution treatment time is 8h.
[0033] In step 2, artificial aging treatment is performed on the WE43 magnesium alloy at 250°C, and the aging time is determined to be 10h, 12h, 14h, 16h, and 18h. By observing and analyzing the microstructure of the WE43 magnesium alloy after aging treatment and combining its mechanical properties, the optimal aging treatment time is determined to be 14h.
[0034] In some embodiments, the WE43 rare earth magnesium alloy is placed in a DHG-9030A electric heating forced air drying oven and kept at 120° C. for 0.5 h before solution treatment.
[0035] In some embodiments, before the solution treatment of WE43 rare earth magnesium alloy, the muffle furnace is preheated to 120°C and kept warm for 0.5h to remove all water vapor in the device. The purpose is to prevent the hydrogen generated by the contact between the molten magnesium matrix and water vapor at high temperature from reacting rapidly with the oxygen in the surrounding air, and the rapid vaporization of liquid water, which may cause explosions, and the magnesium alloy castings may have defects such as shrinkage, which may affect the alloy properties.
[0036] In the following examples, a VHX-5000 digital microscope produced by Keyence Corporation of Japan was used to observe the metallographic microstructure of the alloy after heat treatment.
[0037] In the following examples, the mechanical properties were tested using a Gleeble-3800 thermal simulation testing machine produced by Dynamic System, Inc., USA.
[0038] Example 1
[0039] The rare earth magnesium alloy sample with a size of 10mm×10mm×5mm has chemical compositions and their mass fractions of Y: 3.82%, Zr: 0.43%, Gd: 1.48%, Nd: 2.47%, Ni: 0.001%, Fe: 0.001%, Cu: 0.003% and the remainder of Mg and impurity elements. Before heat treatment, the surface was placed in a DHG-9030A electric heated blast drying oven at 120°C for half an hour, and the sample was placed in a KSL-1500X muffle furnace. Since the reactor is not a vacuum environment, in order to prevent material oxidation, this experiment took fine quartz sand in the crucible, buried the material in the quartz sand, and covered it with pyrite for heat treatment. After that, the sample was heated to 525°C and kept warm for 8h, and then the alloy was quickly cooled by water quenching at room temperature. Subsequently, the alloy after solid solution treatment was aged, and the aging treatment temperature was set to 250°C and the time was set to 10h. The metallographic structure of the sample after heat treatment is as follows Figure 1 Its stress-strain relationship is shown in Figure 4 and 5 shown.
[0040] Example 2
[0041] The rare earth magnesium alloy sample with a size of 10mm×10mm×5mm has chemical compositions and their mass fractions of Y: 3.82%, Zr: 0.43%, Gd: 1.48%, Nd: 2.47%, Ni: 0.001%, Fe: 0.001%, Cu: 0.003% and the remainder of Mg and impurity elements. Before heat treatment, the surface was placed in a DHG-9030A electric heated blast drying oven at 120°C for half an hour, and the sample was placed in a KSL-1500X muffle furnace. Since the reactor is not a vacuum environment, in order to prevent material oxidation, this experiment took fine quartz sand in the crucible, buried the material in the quartz sand, and covered it with pyrite for heat treatment. After that, the sample was heated to 525°C and kept warm for 8h, and then the alloy was quickly cooled by water quenching at room temperature. Subsequently, the alloy after solid solution treatment was aged, and the aging treatment temperature was set to 250°C and the time was set to 12h. The metallographic structure of the sample after heat treatment is as follows Figure 2 Its stress-strain relationship is shown in Figure 4 and 5 shown.
[0042] Example 3
[0043] The rare earth magnesium alloy sample with a size of 10mm×10mm×5mm has chemical compositions and their mass fractions of Y: 3.82%, Zr: 0.43%, Gd: 1.48%, Nd: 2.47%, Ni: 0.001%, Fe: 0.001%, Cu: 0.003% and the remainder of Mg and impurity elements. Before heat treatment, the surface was placed in a DHG-9030A electric heated blast drying oven at 120°C for half an hour, and the sample was placed in a KSL-1500X muffle furnace. Since the reactor is not a vacuum environment, in order to prevent material oxidation, this experiment took fine quartz sand in the crucible, buried the material in the quartz sand, and covered it with pyrite for heat treatment. After that, the sample was heated to 525°C and kept warm for 8h, and then the alloy was quickly cooled by water quenching at room temperature. Subsequently, the alloy after solid solution treatment was aged, and the aging treatment temperature was set to 250°C and the time was set to 14h. The metallographic structure of the sample after heat treatment is as follows Figure 3 Its stress-strain relationship is shown in Figure 4 and 5 shown.
[0044] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the protection scope of the present invention.
Claims
1. A WE43 rare earth magnesium alloy, characterized in that: The components are calculated by mass percentage as follows: Y: 3.82%, Zr: 0.43%, Gd: 1.48%, Nd: 2.47%, Ni: 0.001%, Fe: 0.001%, Cu: 0.003%, and the remainder is Mg and unavoidable impurity elements.
2. The WE43 rare earth magnesium alloy according to claim 1, characterized in that: The WE43 rare earth magnesium alloy is an extruded WE43 rare earth magnesium alloy.
3. The step heat treatment method of WE43 rare earth magnesium alloy according to claim 1 or 2, characterized in that: The following steps are involved: Step 1: burying the WE43 rare earth magnesium alloy in quartz sand, laying pyrite sand on the upper layer, placing the whole in a muffle furnace, and heating for solid solution treatment. The solid solution treatment process includes: heating the WE43 rare earth magnesium alloy to 500-550° C. and then keeping it warm for 4-12 hours; Step 2: performing artificial aging treatment on the solution treated WE43 rare earth magnesium alloy, wherein the artificial aging treatment process comprises: cooling the WE43 rare earth magnesium alloy to 200-300° C., keeping the temperature for 10-18 hours, and then placing the alloy in air for natural cooling.
4. The step heat treatment method of WE43 rare earth magnesium alloy according to claim 3, characterized in that: KSL-1500X box-type muffle furnace was used to carry out solution treatment and artificial aging treatment on WE43 magnesium alloy.
5. The step heat treatment method of WE43 rare earth magnesium alloy according to claim 3, characterized in that: Before the solution treatment, the WE43 rare earth magnesium alloy was placed in a DHG-9030A electric heating blast drying oven and kept at 120° C. for 0.5 h.
6. The step heat treatment method of WE43 rare earth magnesium alloy according to claim 3, characterized in that: Before the solution treatment of the WE43 rare earth magnesium alloy, the muffle furnace is preheated to 120° C. and kept warm for 0.5 h.
7. The step heat treatment method of WE43 rare earth magnesium alloy according to claim 3, characterized in that: In step 1, the solution treatment process includes: heating the WE43 rare earth magnesium alloy to 525° C. and then keeping the temperature for 8 hours.
8. The step heat treatment method of WE43 rare earth magnesium alloy according to claim 3, characterized in that: In step 2, the artificial aging treatment process includes: cooling the WE43 rare earth magnesium alloy to 250° C. and then keeping the temperature for 14 hours.